Impact of meteorological factors on influenza incidence in Wuxi from 2014 to 2019: a time series and comprehensive analysis - He, Menglan; Wang, Yan; Ding, Xinliang; Gao, Yumeng; Shi, Chao (Frontiers in Public Health, 2025)
BackgroundAlthough the association between meteorological factors and influenza was numerously documented, the results are inconsistent, requiring a meta-analysis for synthesis. A recent analysis of the association between influenza and meteorological factors was conducted in Wuxi, China.MethodsMeteorological data and laboratory-confirmed influenza cases from 2014 to 2019 were collected in Wuxi. The exposure-response relationship was analyzed using a generalized additive model. Then we performed subgroup analysis based on age and gender. Finally, meta-analysis was utilized to aggregate the total influence of meteorological factors on influenza.ResultsA total of 5,306 influenza cases were reported. Seven influenza peaks, observed every winter to spring and only one summer (2015), were noted. For a unit increase in weekly average pressure, temperature, wind speed, relative humidity, precipitation, and sunshine duration, the risk of influenza increased by 7.37%, decreased by 8.39%, decreased by 33.83%, increased by 6.44% when relative humidity was >68.86%, increased by 19.91% when precipitation was ≤ 6.13 mm, and decreased by 11.41% when sunshine duration was ≤ 6.30 h, respectively. No significant gender differences were observed. The impacts of air pressure, temperature, precipitation, and sunshine duration on children aged 3–14 were greater than on other age groups. Compared with the meta-analysis, the pooled effect of ambient temperature was consistent. In subgroup and meta-regression analysis, significant differences were found in the children group.ConclusionThis study provides further insight into the effects of meteorological factors on influenza incidence, especially the impact on children, helping enhance the level of influenza monitoring and early warning research.